Anatomy of extrafloral nectaries in Fabaceae from dry-seasonal forest in Brazil - Mello, Yanna Carla da Silva; Machado, Silvia Rodrigues [UNESP]; Alves, Marccus Vinícius da Silva (Oxford University Press (OUP), 2010)
Extrafloral nectaries (EFNs) are found in many species of Fabaceae. The aim of this work is to describe the internalmorphology of the EFNs from species of Fabaceae found in areas of dry-seasonal forest in north-eastern Brazil. Allspecies of Fabaceae with EFNs found were collected and samples were submitted to conventional techniques foranatomical and scanning electronic microscopy analysis. EFNs were found in 35 species, of which 32 wereexamined anatomically. All types have epidermal cells, secretory tissues and vascular bundles in the EFNs.Sclerenchymatous cells were found between the secretory tissues and the vascular tissues, with a few exceptions.The function of these cells is not clear; however, a role in the transportation of the sap in the nectary or with thesupport of the secretory tissue is possible. The nectar is released through glandular trichomes, secretory pores oreven by breaking the epidermal cells and cuticle. The internal patterns found in the EFNs from different speciesand genera can provide important information for taxonomic and evolutionary studies in the family.
Keywords: Caatinga; Legumes; Secretory structures